2009
DOI: 10.1111/j.1742-4658.2009.07234.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hfq on global gene expression and virulence in Neisseria gonorrhoeae

Abstract: Hfq is an RNA chaperone that functions as a pleiotropic regulator for RNA metabolism in bacteria. In several pathogenic bacteria, Hfq contributes indirectly to virulence by binding to riboregulators that modulate the stability or translation efficiency of RNA transcripts. To characterize the role of Hfq in the pathogenicity of Neisseria gonorrhoeae, we generated an N. gonorrhoeae hfq mutant. Infectivity and global changes in gene expression caused by the hfq mutation in N. gonorrhoeae strain MS11 were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Consequently, an hfq mutant of S. Typhimurium was found to be highly attenuated in a mouse infection model (23). Similarly, experiments employing murine or rat infection models revealed a role of Hfq in the virulence of several pathogenic bacteria (24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Consequently, an hfq mutant of S. Typhimurium was found to be highly attenuated in a mouse infection model (23). Similarly, experiments employing murine or rat infection models revealed a role of Hfq in the virulence of several pathogenic bacteria (24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…The transcriptional regulators Hfq, PhoP (MisR), and Lrp were upregulated during prolonged (Ͼ24 h) cocultivation, establishing their importance in modulating genome-wide patterns of gene expression during established colonization. Hfq binds small RNAs and is widely involved in gene regulation: hfq mutants are attenuated for epithelial cell adherence (48). Employing proteomic approaches, two studies using meningococcal hfq mutants have identified a number of deregulated proteins (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of Hfq as a virulence regulator is not universal among pathogens. For example, in Staphylococcus aureus, an hfq mutant, virulence for the worm Caenorhabditis elegans was not affected (48), and in Neisseria gonorrhoeae, the virulence of an hfq mutant was not altered in cell culture models (49).…”
Section: Discussionmentioning
confidence: 99%